IMPACT OF INFORMAL SECTOR RECYCLING ACTIVITIES OF WASTE SCAVENGING IN GOMBE METROPOLIS - R. D. Abu; G. U. O. Michael (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
Informal recycling activities of waste scavenging are associated with health risk and social problems. Despite these problems, a sizeable number of the urban poor population in Nigeria depends on recycling materials from waste for their livelihoods and household poverty reduction. This study utilized data collected from questionnaire survey, in-depth discussion guides and open-ended interviews to examine the demographic characteristics of waste scavengers, income levels from scavenging activities, the working conditions and problems of waste collectors and pickers in Gombe metropolis. For the purpose of data collection, the researcher enumerated 300 waste pickers across the 10 wards that make up the study area and using systematic sampling technique, 150 respondents were selected for the study. The socio-economic and sociodemographic characteristics of scavengers differ from location to location and the findings of this study reveals that 92% male and 8% female respondents of the urban poor engage in waste scavenging activity as an option of securing their livelihood. The 150 informal waste collector participants in the study recovered about 151,200 tons of recyclable materials from the waste stream on an annual basis and this translate to an income of ₦2,186,000.00 on a monthly basis with 34.7% of the respondents earning above the ₦18,000 national minimum wage with their economic impact estimated at ₦26,232,000 annually. It also shows that engagement in waste scavenging activities provides income comparable with national minimum wage in the public sector and thus helps in poverty reduction. The recovered items reduces the volume of the waste stream at the final dump sites and serve as raw material input for some industrial processes particularly in the metal conversion industries. Based on the findings, recommendations on the restructuring and integration of informal recycling with the formal waste management sector in order for it to be lucrative to generate more jobs were made.